KEARIFAN LOKAL TRADISI SEDEKAH BUMI DALAM PEMBENTUKAN KARAKTER MASYARAKAT DIBEE LAMONGAN - Moh. Rizki Maulana; Shintia Ananda Polisya; Siti Nur Qoimah; Anang Dony Irawan (Jurusan P. IPS, FKIP, Universitas Mataram, 2022)
The State of Indonesia has a culture that is very diverse in form and characteristics of each. At the local level, there is a tradition of giving alms to the earth which is carried out by the people of Dibee Village, Kalitengah District, Lamongan Regency. It is interesting to know how this tradition has continued until now, and the values ​​contained therein. Behind that, the tradition of giving alms to the earth is an expression of the people's gratitude for the sustenance to God Almighty. More than that, through this tradition, with prayers, residents hope that next year's harvest will be better. This value is related to the farming culture which is the main livelihood of the community. In addition, through this tradition, the community maintains an emotional bond with nature and respects the surrounding environment. Sociologically, the almsgiving earth tradition has values ​​contained in Pancasila, namely building togetherness among residents of Dibee Village, Kalitengah District, Lamongan Regency.